Career Perspectives for Pediatric Orthopaedic Trainees and Early Practitioners: A Panel Discussion - Jeffrey B. Peck, MD; William Cutchen, MD; Lee Haruno, MPH; Dustin Greenhill, MD; Karen Bovid, MD; Brandon Ramo, MD (Journal of the Pediatric Orthopaedic Society of North America)
The life of a pediatric orthopaedic surgeon involves many more challenges than just those seen in our clinics and operating rooms. These begin during fellowship, when key decisions occur regarding training and the development of mentor and peer relationships. Then, selection of a surgeon's first job opportunity and ensuing practice development involve significant potential career turning points. Our panel of young surgeons offers thoughts and advice on these situations, hoping that current and future trainees will benefit from the knowledge gained through their experience in entering and beginning a successful career in pediatric orthopaedics. Key Concepts: (1) When selecting a fellowship, it is valuable to understand one's learning style and to consider family needs. (2) After discovering what positions may be available, match each potential position's professional and personal opportunities with your needs. (3) Your initial practice will evolve to your ideal professional endpoint over years of effort and development. (4) The optimal work-life relationship is possible with good communication with your partner/family and with a good team of supporting healthcare staff around you. (5) Regular attendance at the POSNA annual meeting and involvement in committee work can be a resource and provide tremendous professional satisfaction.